Bumps along the road of the tiny house movement: practitioner notes with critical reflections. Issue 3 (2nd October 2018) - Alexander, Samuel; Gleeson, Brendan; Coupe, Tom; Matyevich, Nick; Scott, Rob; Schultz, Fred
ABSTRACT: This article begins by sharing practical insights and learnings from tiny house builders, highlighting some promising approaches to construction, as well as some challenges faced by the emerging tiny house movement. The article also offers a conceptually driven appraisal of this potentially important new housing form that raises serious questions about planning and urban policy. The aim is to present a grounded review of the tiny house movement, and its wider policy resonances, rooted in an empirical review of current practice. After the empirical practice notes are presented, the article concludes by going beyond building, construction, and regulatory issues and offers some critical reflections on the promise and limitations of the tiny house movement. These intricacies and potential difficulties include frictions with wider housing and urban policies in Australia, especially those that have favoured transition to higher residential densities and which are themselves fraught with challenges especially around social equity. In offering a sympathetic critique of tiny houses and asking some hard questions, this review and analysis seeks to present a richer and fuller understanding of the tiny house movement in a way that helps the movement progress and avoid unnecessary pitfalls.